Validasi Pengembangan Media Edukasi Protokol Covid Berbasis Sablon dalam Bentuk Pouch Bagi Siswa Sekolah Dasar di Kota Padang - Fitri Maiziani; Dedi Supendra (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2021)
The Covid-19 pandemic has had an impact on all lines of life, including the education aspect. Entering the New Normal Era, the implementation of learning in schools is regulated following the health protocol. The purpose of this study was to see the validity of the development of Screen Printing-Based Covid Protocol Educational Media in Pouch Form for Elementary School Students in Padang City. The research method used is development research with a 4D model. This research procedure uses quantitative and qualitative data by using research instrument validity questionnaire sheets distributed to experts (validators). The results of this study obtained validity from very valid health experts, from valid media experts, from valid graphic design experts, and from Very Valid Elementary School Education experts